Liquidity, Solvability, and Profitability Ratio Analysis towards Financial Performance - Bagus Sholaeman; Risal Rinofah; Alfiatul Maulida (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
A cooperative is a collection of people with social characteristics who work together based on the principles of kinship and cooperation to advance the interests of cooperative members. This study aims to analyze the financial performance of BMT Projo Artha Sejahtera in Bantul by using financial ratios. The analytical method used in this research is a descriptive quantitative analysis using the measurement of liquidity ratios, solvency ratios, and profitability ratios. The analytical tool used in paying short-term obligations by using the Current Ratio and Quick Ratio of the liquidity ratio. Based on the research results, it can be concluded that seen from the liquidity ratio, the Current Ratio and Quick Ratio have decreased every year. The increase in this ratio shows that the company is not performing well because the cooperative has not been able to pay its current obligations. Judging from the solvency ratio, the Total Debt to Total Assets Ratio and Total Debt to Equity Ratio has decreased. The decrease in this ratio indicates a good company performance because of the smaller financial risk. Judging from the profitability ratio, Return On Assets and Return On Equity also increased. The increase in this ratio indicates that performance is good because it is maximum in generating profits.